2004
DOI: 10.1016/j.jcrysgro.2004.06.044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcium cations on the precipitation of barium sulfate 2: calcium ions in the presence of organic additives

Abstract: Calcium ions have been implicated in changing the precipitation of barium sulfate when organic additives are present, although whether it inhibits or promotes nucleation and/or growth has been disputed in the literature. We conducted a thorough investigation into the effect of calcium when additives are present and show that calcium cations do indeed promote nucleation of barium sulfate particles when compared to the appropriate control. This result is independent of the analytical method (conductivity or turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 16 publications
(37 reference statements)
4
32
1
Order By: Relevance
“…5,6 In addition, the ability of these additives to inhibit in the presence of other ions is assessed. As with previous work in this area, 16,17 the choice of the standard by which to compare the results is shown to significantly affect the interpretation of the results.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…5,6 In addition, the ability of these additives to inhibit in the presence of other ions is assessed. As with previous work in this area, 16,17 the choice of the standard by which to compare the results is shown to significantly affect the interpretation of the results.…”
Section: Introductionmentioning
confidence: 73%
“…We hypothesized that for EDTA, complexation with calcium may have been the cause (implying that the complexed EDTA either did not interact with the barite or was completely incorporated at a % inhibition ) ((r Zn -r Zn+organic )/r Zn ) × 100 (2) very early stage of precipitation). 17 We hypothesize that something similar is occurring to the HDTMP + Zn 2+ ion system. The second comparison we can make is to compare HDTMP + (170 ppm) Zn 2+ at a particular HDTMP concentration versus HDTMP + Na + at the same HDTMP concentration and with sufficient Na + ions to match the ionic strength (this would then assume that the two systems at the same ionic strength would have the same supersaturation, which may not necessarily be the case).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…8, and it can be seen that EDTA is almost completely complexed with calcium and so very little barium ion complexation is expected to occur. As shown in [31] the presence of calcium ions and EDTA during barite precipitation leads to a lower inhibitory response. Thus, the presence of calcium ions increases the de-supersaturation rate when compared to an appropriate control [31].…”
Section: The Effect Of Calciummentioning
confidence: 85%
“…It has been shown that calcium ions impart their own substantial impact on barium sulfate precipitation [25] and that this behaviour changes when EDTA is also present [31]. When comparing solutions with and without calcium ions present, inhibitors can appear to inhibit better in the presence of calcium ions.…”
Section: The Effect Of Calciummentioning
confidence: 99%